1979
DOI: 10.1017/s0016672300019352
|View full text |Cite
|
Sign up to set email alerts
|

Abuffspore colour mutant inSordaria brevicollisshowing high-frequency conversion

Abstract: A buff-yellow spore mutant combination in :Sonlono brevicollis, where all four individual spore genotypes and all three non-aberrant tetrad types namely parental ditypes, non-parental ditypes and tetratypes-can be directly detected and scored under the microscope, is described. Aberrant segregation octads too are directly and easily detected in this system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
20
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…The 8-base-pair (bp) Chi sequence in Escherichia coli is the most fully characterized recombination hotspot, shown to increase recombination in bacteriophage lambda and E. coli DNA via the RecA-RecBCD pathway (reviewed in reference 34). Recombination hotspots have also been described in fungi (12,25) and in mammalian cells (37; W. P. Wahls, L. J. Wallace, and P. D. Moore, Cell, in press).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The 8-base-pair (bp) Chi sequence in Escherichia coli is the most fully characterized recombination hotspot, shown to increase recombination in bacteriophage lambda and E. coli DNA via the RecA-RecBCD pathway (reviewed in reference 34). Recombination hotspots have also been described in fungi (12,25) and in mammalian cells (37; W. P. Wahls, L. J. Wallace, and P. D. Moore, Cell, in press).…”
mentioning
confidence: 98%
“…The 8-base-pair (bp) Chi sequence in Escherichia coli is the most fully characterized recombination hotspot, shown to increase recombination in bacteriophage lambda and E. coli DNA via the RecA-RecBCD pathway (reviewed in reference 34). Recombination hotspots have also been described in fungi (12,25) and in mammalian cells (37; W. P. Wahls, L. J. Wallace, and P. D. Moore, Cell, in press).A short fragment of mammalian DNA from the human ,Bglobin gene cluster, MG-1 (29), promotes unusual recombination events during yeast meiosis (41). Molecular evidence indicates that the DNA sequence responsible is an 80-bp stretch of the simple repeating dinucleotide polydeoxythymidylic-guanylic polydeoxyadenylic-cytidylic acid, abbreviated hereafter as d(TG)n.…”
mentioning
confidence: 99%
“…Mutations or strain differences identifying hot spots were originally found in fungi (Angel et al 1970;Gutz 1971;MacDonald and Whitehouse 1979) and have been subsequently found in a variety of organisms from bacteriophages (Lain et al 1974~ Stahl et al 1975) to humans (Wahls et al 1990a). Known recombination hot spots stimulate recombination up to 30-fold and exert their effects within a few tens of kilobase pairs.…”
mentioning
confidence: 99%
“…Several meiotic recombination hot spots have been identified, including the M26 mutation of ade6 in Schizosaccharomyces pombe (8), the YS17 mutation of the buff spore color locus in Sordaria brevicolis (18), and the cog' mutation in Neurospora crassa (1). In addition, the HOT] gene in the rRNA gene cluster in Saccharomyces cerevisiae functions in cis to stimulate mitotic recombination (13).…”
mentioning
confidence: 99%